Effect of Sr Content on Microstructure and Electrical Properties of Lead-free Ba1-xSrxTiO3 thin Films - Hien, Vu Thu; Thi Minh Phuong, Nguyen; Ngoc Hung, Vu (VNU Journal of Science: Mathematics - Physics, 2025)
Lead-free barium  titanate based Ba 1-x Sr x TiO 3 thin films (x = 0 ÷ 0.45) have been deposited onto Pt/Ti/SiO 2 /Si(100) substrate via sol–gel technique. The films were crystallized at temperature of 650 °C for 30 min in the air. The experimental data displayed that microstructure, dielectric and ferroelectric properties of the films were strongly influenced by the Sr concentration. All the films are well formed in a polycrystalline perovskite phase with a shift of diffraction planes toward larger 2θ as increasing Sr content. High resolution scanning electron microscopy images as well as cross-section profile indicate a dense structure, clear grains and a sharp interface between the film and Pt electrode. However, the shape and grain size change among Sr-doped films. Series data on capacitance ˗ voltage measurements reveal that dielectric constant (ε)  increases with Sr-dopant concentration while  loss tangent  (tanδ) decreases. The optimal dielectric properties are found for Ba 0.55 Sr 0.45 TiO 3 (x= 0.45), while Ba 0.65 Sr 0.35 TiO 3 (x= 0.35) thin films perform better polarization properties with the maximum polarization of 8.07 mC/cm 2 under applied electric field of 1,000 kV/cm.